(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Traumatic brain injury (TBI) has serious long-term consequences, including chronic encephalopathy with various syndromes. Traumatic brain injury (TBI) is one of the most important aspects of research in neurological practice, due to the high frequency, difficulties of diagnosis and severity of its course, often fatal outcome. It has a generalized effect on the body, causing a general adaptive reaction, manifested in a complex of pathophysiological, biochemical and morphofunctional changes not only in the area of ​​direct mechanical damage, but also in the nervous, endocrine, cardiovascular and other systems. Mostly men die from this injury and more often of working age, which gives the whole problem social significance. With autonomic dysregulation, angiodystonia with altered arterial tone is observed. Epileptic syndrome is also accompanied by angiodystonic disorders. Liquorodynamic disorders are characterized by increased peripheral resistance, venous discirculation and asymmetry of blood flow in various vascular beds in cerebral focal syndrome. These hemodynamic changes indicate the need for differentiated therapy depending on the leading clinical syndrome.